Southcliffe [videorecording (DVD)] - Grisoni, Tony; Kinnear, Rory, 1978-; Harris, Sean, 1966-; Henderson, Shirley, 1965-; Yusef, Anatol; Marsan, Eddie; Erdély, Mátyás, 1976-; Greenway, Daniel (BBC, 2019)
"Exactly a year after he reported on a killing spree in the town of his unhappy childhood, English journalist David Whitehead ... returns to the scene of the crime in response to an anonymous message. Someone--who?--warns that the killing is about to begin again. Is tragedy somehow woven into the fabric of the town? Will the people closest to last year's victims ever find ways to heal their broken lives?"--